APPLICATION OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL IN SOCIAL SCIENCE LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES CLASS IV AT STATE 39 PRIMARY SCHOOL BANDA ACEH CITY - Rahma, Siti; Husin, M.; Yamin, M. (Elementary Education Research, 2024)
In social studies learning, student learning outcomes are still relatively low due to the lack of student involvement in the teaching and learning process. The formulation of the problem in this research is how teacher activities, student activities and learning outcomes apply the Contextual Teaching and Learning (CTL) model to social studies learning theme 8 subtheme 1 learning 3. This research aims to improve teacher activities, student activities and students' social studies learning outcomes class IV of SD Negeri 39 Banda Aceh City. This research uses the classroom action research (PTK) method with the Kemmis McTaggart model research design, this research uses three cycles. The subjects in this research were 26 class IVA students, consisting of 15 men and 11 women. The data collection techniques used are observation and tests. The data analysis technique uses qualitative descriptive analysis. Observation results show that there was an increase in teacher activity in cycle I with an average value of 2.3 (fair), in cycle II with an average value of 3.1 (good) and in cycle III with an average value of 3.6 ( Good). Student activity also increased, namely in cycle I with an average score of 2 (fair), in cycle II with an average score of 2.85 (good) and in cycle III with an average score of 3.57 (good). Student learning outcomes became better, namely in cycle 1 they got an average score of 50.3 with a completion percentage of 46.1%, in cycle II they got an average score of 71.1 with a completion percentage of 69.2% and in cycle III they got a score an average of 77.6 with a completion percentage of 88.4%. This improvement has reached indicators of success or completion, from the results of the data analysis it can be concluded that the application of the Contextual Teaching and Learning (CTL) model in social studies subjects theme 8 subtheme 1 learning 3 can increase teacher, student activity and student learning outcomes.